Inflammasome activity regulation by PUFA metabolites - Atalay Ekiner, Sinemyiz; Gęgotek, Agnieszka; Skrzydlewska, Elżbieta (Frontiers in Immunology, 2024)
Oxidative stress and the accompanying chronic inflammation constitute an important metabolic problem that may lead to pathology, especially when the body is exposed to physicochemical and biological factors, including UV radiation, pathogens, drugs, as well as endogenous metabolic disorders. The cellular response is associated, among others, with changes in lipid metabolism, mainly due to the oxidation and the action of lipolytic enzymes. Products of oxidative fragmentation/cyclization of polyunsaturated fatty acids (PUFAs) [4-HNE, MDA, 8-isoprostanes, neuroprostanes] and eicosanoids generated as a result of the enzymatic metabolism of PUFAs significantly modify cellular metabolism, including inflammation and the functioning of the immune system by interfering with intracellular molecular signaling. The key regulators of inflammation, the effectiveness of which can be regulated by interacting with the products of lipid metabolism under oxidative stress, are inflammasome complexes. An example is both negative or positive regulation of NLRP3 inflammasome activity by 4-HNE depending on the severity of oxidative stress. 4-HNE modifies NLRP3 activity by both direct interaction with NLRP3 and alteration of NF-κB signaling. Furthermore, prostaglandin E2 is known to be positively correlated with both NLRP3 and NLRC4 activity, while its potential interference with AIM2 or NLRP1 activity is unproven. Therefore, the influence of PUFA metabolites on the activity of well-characterized inflammasome complexes is reviewed.